Characterization of nCD64 expression in neutrophils and levels of s-TREM-1 and HMGB-1 in patients with suspected infection admitted in an emergency department (2013)
ABSTRACT: Introduction: The nCD64 receptor, the soluble triggering receptor expressed in myeloid cells (s-TREM-1), and the high mobility group-box 1 protein (HMGB-1) have been proposed as significant mediators in sepsis.Objective: To evaluate the prognostic value of these markers in patients with suspected infection recently admitted in an emergency department (ED). Materials and methods: All patients who presented to the ED with suspected infection were eligible for enrollment in this study. Baseline clinical data, Sequential Organ Failure Assessment score (SOFA) score, APACHE II score, HMGB-1 levels, s-TREM-1 levels, and nCD64 levels were analyzed. The HMGB-1 and sTREM-1 serum concentrations were determined using commercially available ELISA kits, and CD64 on the surface of neutrophils was measured by flow cytometry. Results: . A total of 579 patients with suspected infection as their admission diagnosis were enrolled in this study. The median patient age was 50 years (IQR = 35-68). Morbidity during the 28-day followup period was 11.1% (n=64). The most frequent diagnosis at the time of admission was communityacquired pneumonia (CAP) in 23% (n=133) patients, followed by soft tissue infection in 16.6% (n=96), and urinary tract infection in 15% (n=87). After multivariable analysis, no significant association was identified between any biomarker and 28 day mortality. Conclusion: In the context of a tertiary care hospital emergency department in a Latin-American city, the nCD64 receptor, s-TREM-1, and HMGB-1 biomarkers do not demonstrate prognostic utility in the management of patients with infection. The search continues for more reliable prognostic markers in the early stages of infection.